Il mondo scritto dei sensi di Italo Calvino - Danzi, Donatella (Revista de Filología Románica, 2008)
When Italo Calvino died he left unfinished a book about the five senses. Of this interrupted project remain some stories, which have been published in a posthumous work under the title Sotto il sole giaguaro. This article, based on the stories found, contemplates the possible reasons that pushed the writer from Liguria to dedicate a book regarding the sensorial world during his last years.
Keywords: Italo Calvino; Senses; Sotto il sole giaguaro